Fatores que influenciam gestores na adoção de tecnologia da informação em pequenas e médias empresas no setor atacadista da região de Feira de Santana – Ba - BRITO , Arivaldo Ferreira (2018)
This dissertation sought to investigate which factors influence managers to adopt information technology in small and medium-sized companies in the distribution segment of Feira de Santana. Thus, the present study identifies a model of affection of the level of adoption for these small and medium enterprises, using a methodology that contributes to the relevance of this study to the field of Administration and Information Technology, joining these two areas of the knowledge to expand the studies on computational tools to support business management. The results of the descriptive research applied to the target audience, formed by the managers of these companies, demonstrated the great importance in considering specific niches for studies in the area of Information Technology with a view to the organizational management, highlighting the satisfaction of the researched ones when being appreciated by such relevance in the socioeconomic and technological scenario of the region. Based on the analysis of the collected data, a diagnosis of the factors influencing the process of IT adoption by these organizations was obtained, based on the perception made explicit by its managers that act as decision makers in this process, including being able to identify some internal variables and external factors that interfere in their companies regarding the adoption of technology and data ignored by the literature studied.